Penerapan Model Pembelajaran Berbasis Proyek dengan Media Real Lab dan Virtual Lab untuk Meningkatkan Hasil Belajar dan Kemampuan Berpikir Kreatif Siswa dalam Materi Titrasi Asam Basa - Siti Rohana Siregar; Ani Sutiani; Jamalum Purba (Jurnal Inovasi Pembelajaran Kimia (Journal Of Innovation in Chemistry Education), 2019)
This study aims to determine the differences in chemistry learning outcomes and students' creative thinking abilities, as well as the correlation between the two students who are taught using the PjBL learning model using Real Lab media and Virtual Lab. While students' creative thinking skills use observation sheets. The data obtained from the results of the study, namely: (1) To test the hypothesis of student learning outcomes obtained tcount = 2.15 while ttable = 1.998 (2) To test the hypothesis of creative thinking abilities students obtained tcount = 3.40 while ttable = 1.998 ( 3) To test the correlation of creative thinking abilities on student learning outcomes obtained rtable = 0.339 while r1 = 0.391 and r2 = 0.403 with contributions of = 15.26% and 16.27% in each class, the rest is influenced by other variables. So that the conclusion is drawn that there is a difference between learning outcomes and students 'creative thinking abilities that are learned using PjBL learning models by using Real Lab media and Virtual Lab media. There is a positive and significant correlation between students' creative thinking abilities and student learning outcomes in each experimental class.